2020
DOI: 10.26434/chemrxiv.12709751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Hydrogel-Based in Vitro Assay for the Fast Prediction of Antibiotic Accumulation in Gram-Negative Bacteria

Abstract: The pipeline of antibiotics has been for decades on an alarmingly low level. Considering the steadily emerging antibiotic resistance, novel tools are needed for early and easy identification of effective anti-infective compounds. In Gram-negative bacteria, the uptake of anti-infectives is especially limited. We here present a surprisingly simple in vitro model of the Gram-negative bacterial envelope, based on 20% (w/v) potato starch gel, printed on polycarbonate 96-well filter membranes. Rapid permeability mea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 38 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…In addition, we are aware that the differences in biophysical characteristics observed in the model membranes compared to those in whole cells have a high influence on permeability. Nevertheless, it has been demonstrated previously that the permeability through much simpler biomaterials qualitatively correlated with respective bacterial accumulation data, [ 20 ] demonstrating the high importance of sufficient antibiotic uptake to overall intrabacterial accumulation. ( Figure ) In this study, we found that in vitro permeability coefficients matched in bacterio accumulation best when the permeation model was made of OMV from E. coli BL21 DE3 or E. coli BL21 DE3 Omp8 (Figure 9A,B), while purely PL‐containing layers as obtained from liposomes failed to adequately match in vitro permeability with in bacterio accumulation.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…In addition, we are aware that the differences in biophysical characteristics observed in the model membranes compared to those in whole cells have a high influence on permeability. Nevertheless, it has been demonstrated previously that the permeability through much simpler biomaterials qualitatively correlated with respective bacterial accumulation data, [ 20 ] demonstrating the high importance of sufficient antibiotic uptake to overall intrabacterial accumulation. ( Figure ) In this study, we found that in vitro permeability coefficients matched in bacterio accumulation best when the permeation model was made of OMV from E. coli BL21 DE3 or E. coli BL21 DE3 Omp8 (Figure 9A,B), while purely PL‐containing layers as obtained from liposomes failed to adequately match in vitro permeability with in bacterio accumulation.…”
Section: Resultsmentioning
confidence: 78%
“…Importantly, the porin‐blocking study was conducted with 15 × 10 −6 m norfloxacin while the standard permeation assay was conducted with 200 × 10 −6 m compound concentration as reported earlier. [ 20 ] Surprisingly the porin‐deficiency of the BL21 DE3 Omp8‐based model did not lead to a significant drop of permeation for the β ‐lactams, tetracycline and chloramphenicol. This was, however, the case for the liposome‐based models (Section S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations